FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN TENTANG KANKER KULIT DI DESA CIGADOG TAHUN 2020 - Herdiana, Dian; Winata, Arif; Posumah, Wendy Marlin (Universitas Udayana, 2023)
ABSTRACT Background: The prevalence of skin cancer in Indonesia is 5,9 to 7,9% of all cancers per year and is the the third most common type of cancer in Indonesia. Skin cancer is often diagnosed late due to a lack of knowledge about skin cancer. The purpose of this study was to identify factors related to the level of knowledge about skin cancer in Cigadog village in 2020. Methods: This study was an observasional analytic with a cross sectional design. Conducted in September 2020 in Cigadog village, Garut district, West Java by interviewing through a questionnaire in the form of g-forms to people living in Cigadog village who meet the research criteria. Results: From 90 respondents, it was found that the average age of respondents was 36,51 years with the most age group being 18-40 years (early adults). Most education graduates are junior high school with the highest level of education “formal Non-perguruan tinggi”. Many of the respondents work with type of works as household chores and many are not exposed information about skin cancer due to lack of education from health workers. Many respondents are highly knowledgeable. Conclusions: The factor related to the level of knowledge about skin cancer is education (p-value 0,040). Meanwhile, age occupation and information are meaningless. Its hoped that further research and refinement regarding factors related to knowledge of skin cancer are expected. Keywords: Skin Cancer, Knowledge.